Single-stage modified Vienna rectifier SEPIC AC-DC LED driver - Kenan Gürçam; M. Nuri Almalı (Ain Shams Engineering Journal)
This paper presents an innovative approach by combining a modified first-stage Vienna rectifier with a single-stage SEPIC converter. The proposed Vienna rectifier structure significantly reduced the switch stress. This allows the use of switches with low voltage values and reduced resistances. The use of a non-electrolytic capacitor in the output stage contributed to extending the life of the LED driver. These features enhance the efficiency of the proposed driver. The recommended LED driver complies with the mandatory standards specified in IEC61000-3–2 for Class C loads. To verify the effectiveness of this proposed system, a setup of an 18 W LED driver operating was presented and simulated. This research aims to address power factor, switch stress, and harmonic distortion issues commonly associated with LED driver circuits, contributing to more efficient and compatible LED lighting systems.